Processos verdes de extração de produtos naturais de materiais vegetais com ultrassom e micro-ondas - Ferreira, Daniele de Freitas (2020)
The market of natural ingredients has been increasing worldwide in the last years, and, as a consequent the development of efficient extraction methods can be a current challenge for food, chemicals and pharmaceutical industries. In this way, the employment of microwave and ultrasound technologies can be a promising alternative, mainly for providing high efficiency, fast processes and the high quality of obtained products. Thereby, the aim of this work was to promote the extraction of bioactive compounds from different vegetal material using microwave and ultrasound. The employment of the extraction method, microwave hydrodiffusion and gravity (MHG), showed advantageous in obtaining phenolic extracts as well as essencial oils. Its use allowed the simultaneous recovery of essential oil and aqueous extract from rosemary in a unique step process, fast and without organic solvent. Beyond that, the use of MHG also provided the obtention of an extract from olive leaf rich in phenolic compounds, through a multistep approach that resulted in the enhancement of process efficiency. As a strategy to accelerate the essential oil extraction, the ultrasound showed promising results in this study. The use of ultrasound as a pre-treatment prior to hydrodistilation step allowed a significant reduction of process time and energy saving and, the recovery of essential oil from basil, lemongrass and lemon peel of high quality. In addition, ultrasound also presented a good performance in the extraction process of pumpkin seed. The use of this technology combined with a mixture of ternary solvent provided a fast extraction of lipophilic and hydrophilic compounds of the seeds. It is important to note that, in all studies, the product obtained by the use of ultrasound or microwave presented higher antioxidant activity in comparison to those obtained by conventional methods. Furthermore, the use of this alternative technologies promoted a considerable reduction in the time of process, demonstrating the great potential of proposed methods